СRIME CONNECTED WITH TRAFFICKING IN PERSONS IN THE MIRROR OF VICTIMOLOGICAL STATISTICS OF THE REPUBLIC OF KAZAKHSTAN - Bekmagambetov, Alimzhan (Administrative and Criminal Justice, 2017)
In article aimed on researching victimological aspects of the crime connected with trafficking in persons in the Republic of Kazakhstan through the prism of official statistics of the UN Committee on Drugs and Crime, the International Organization for Migration in Kazakhstan, the Commission on Human Rights under the President, the Committee on Legal Statistics and Special Accounts of the Prosecutor General's Office and the Supreme Court of the Republic of Kazakhstan. . The novelty of this publication is that the author for the first time in the country attempted a comprehensive study of diverse empirical material, doctrinal views, expert assessments of practitioners and the formulation of conclusions of a theoretical and applied nature. Тhe author comes to a conclusion about lack of a united integral victimological picture concerning the group of criminal acts connected «with human turnover». In the global plan, the opinion on further development of practices in the sphere of conceptual justification and the practical embodiment of victimological policy is supported.